School Bullying—The Silent Epidemic: A Cross-Sectional Study of Factors Associated With Peer Victimization Among Lebanese Adolescents - Obeïd, Sahar (Journal of interpersonal violence, 2022)
The objective of this study was to evaluate bullying at school and identify the factors associated with it among a sample of Lebanese school adolescents. A cross-sectional study was carried out between April 2014 and June 2014, using a convenient sampling of Lebanese students in private schools from Beirut and Mount Lebanon. The results showed that 712 (18.1%) adolescents had been bullied in the past 2 months (95% CI [0.169, 0.192]). A backward logistic regression, taking “being bullied in the last 2 months” as a dependent variable, showed significantly lower odds of being bullied in the last 2 months in those who find it easy (adjusted odds ratios [aOR] = 0.434) and very easy (aOR = 0.391) to talk to their father, and having some close male or female friends compared with none. Furthermore, significantly higher odds of being bullied were found among males compared with females (aOR = 0.664), having a best friend who smokes sometimes compared with never (aOR = 1.389), and a father who drinks everyday compared with never (aOR = 1.621). This study was able to shed light on a problem that sometimes goes silent in schools and has a negative impact on the mental health of teenagers. Indeed, the results of our study showed that peer victimization was closely linked to clinically relevant mental health issues. In addition, factors such as parental and peer support could protect against the negative effects of bullying.